MICROFINANCE AND INCOME LEVEL IN NIGERIA - Sheriff Akanji IBRAHIM (Malete Journal of Accounting and Finance, 2024)
In underdeveloped nations, microfinance has drawn a lot of attention as an effective tool for reducing poverty and promoting economic empowerment as potent stimulators of income level. This is achieved through channelization of credit to the poor and unbanked segment of the economy to help them engage in new productive business activities or to sustain or expand existing ones. This paper examines the relationship between microfinance banks activities and income level in Nigeria, using per capita income (PCI) as the dependent variable, and microfinance banks activities such as loan and advances (LADV), deposit mobilization (TDEP) and other non-banking financial activities (NBFIN) as independent variables. The research adopted quantitative design and employed regression analysis in analysing the effect of microfinance bank activities on income level in Nigeria between 1995 to 2022. The findings were that the activities of microfinance banks account for more than 53% of the variation in per capita income. The paper thus concluded that these institutions make financial markets accessible to individuals and households so they can finance investments and boost their per capita income. It recommends that microfinance banks should seek to mobilize deposits from the underserved demography of the economy to help the economically active but underserved segment of Nigerian society raise their standard of living.